Sistem Registrasi Kamar Hotel - Alfi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2021)
The Hotel Room Registration System aims to streamline the booking and management of hotel rooms. This system provides a user-friendly interface for customers to check room availability, make reservations, and manage their bookings. Additionally, it allows hotel staff to efficiently handle room assignments, monitor occupancy rates, and manage customer information. By integrating functionalities such as real-time availability checks, automated booking confirmations, and detailed customer records, the system enhances customer satisfaction and operational efficiency. The system also includes features for reporting and analytics, enabling hotel management to make informed decisions based on real-time data. Furthermore, the system supports integration with online payment systems, offering greater flexibility for customers. Overall, the Hotel Room Registration System contributes to a seamless and efficient hotel management process, improving both customer experience and hotel operations.